Promising phytochemical responses of Achyrocline satureioides (Lam.) DC. under various farming conditions - Garcia, Daniel [UNESP]; Furlan, Marcos Roberto; Diamante, Marla Sílvia [UNESP]; Minatel, Igor Otavio [UNESP]; Borges, Cristine Vanz [UNESP]; Wu, Ya-ni; Lima, Giuseppina Pace Pereira [UNESP]; Ming, Lin Chau [UNESP] (Elsevier, 2019)
Pharmaceutical industries have a demand for great amounts of Achyrocline satureioides (Lam.) DC., however, most of the raw material commonly is extracted directly from the natural environment without any agronomic management. Faced with this situation, the present study aimed to investigate the total flavonoids and total phenolic compounds, as well as the polyphenolic profile of the branches and inflorescences of a Brazilian local variety of A. satureioides (CPQBA 2), considering different organic fertilizer levels, plant spacing and harvest times. Significant total phenolic compounds were detected in the branches at 240 DAT – days after transplanting (3138.46 mg/100 g) and in the inflorescences of plants cultivated with 30 t ha−1 of organic fertilizer, at 457 DAT (3025.94 mg/100 g). The branches have produced suitable flavonoids content at 320 DAT (236.92 mg/100 g), and the plants cultivated with 30 t ha−1 of organic fertilizer showed major levels of these compounds in the inflorescences at 457 DAT (594.97 mg/100 g). The primary compounds detected in the branches and inflorescences were caffeic acid (105.63 mg/100 g) and 3-O-methylquercetin (323.45 mg/100 g), respectively. Both chemical compounds showed significant changes depending on the farming conditions. These findings showed that, in addition to the inflorescences, the branches of A. satureioides var. CPQBA 2 could also be used as a source of phytochemical compounds by the pharmaceutical industries, avoiding the waste of raw material and providing a new option to growers.
Keywords: 3-O-methylquercetin; Flavonoids; Harvest time; Macela; Organic fertilization; Spacing